2011
DOI: 10.1007/s00208-011-0653-4
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of vanishing at infinity symmetric solutions to the plane stationary exterior Navier–Stokes problem

Abstract: We study a nonhomogeneous boundary-value problem for the steady-state Navier-Stokes equations in a two-dimensional exterior domain with two orthogonal symmetry axes. The existence of a solution which tends to zero uniformly at infinity is proved under suitable parity conditions on the data of the problem. The result is obtained for arbitrary values of the flux of the boundary datum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…For the case u=0 with external force, A. Russo obtained the existence of weak solutions, if |α| is sufficiently small, where α is the total flux from the obstacle defined in (2.14). In particular, if the following outflow condition is satisfied: normalΓn(x)·a(x)ds(x)=0.Next, Galdi [, Section ], A. Russo and Pileckas and R. Russo posed the assumption trueleftThe4.ptset4.ptnormalΩ4.ptis4.ptinvariant4.ptunder4.ptthe4.ptmappingsleftπ1:(x1,x2)(x1,x2),1emπ2:(x1,x2)(x1,x2)with a specific coordinate variables (x1,x2), and the external force f(x)=f1(x),f2(x) is assumed to satisfy the condition {f1(x1,x2)=f1(x1,x2),f2(x1,x2)=f2(x1,x2),…”
Section: Introductionmentioning
confidence: 99%
“…For the case u=0 with external force, A. Russo obtained the existence of weak solutions, if |α| is sufficiently small, where α is the total flux from the obstacle defined in (2.14). In particular, if the following outflow condition is satisfied: normalΓn(x)·a(x)ds(x)=0.Next, Galdi [, Section ], A. Russo and Pileckas and R. Russo posed the assumption trueleftThe4.ptset4.ptnormalΩ4.ptis4.ptinvariant4.ptunder4.ptthe4.ptmappingsleftπ1:(x1,x2)(x1,x2),1emπ2:(x1,x2)(x1,x2)with a specific coordinate variables (x1,x2), and the external force f(x)=f1(x),f2(x) is assumed to satisfy the condition {f1(x1,x2)=f1(x1,x2),f2(x1,x2)=f2(x1,x2),…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the higher dimensional cases, less is known so far for the case of two-dimensional exterior domains. Indeed, for the two-dimensional exterior problem the unique existence of stationary flows decaying at spatial infinity has been achieved mainly under some symmetry conditions on both the domain and given data; see Galdi [14], Russo [41], Yamazaki [46], and Pileckas and Russo [40], and see also Nakatsuka [38] for a recent uniqueness result. In particular, Yamazaki [46] obtained the decay order O(|x| −1 ) for the stationary solutions constructed there.…”
Section: Theorem 13 There Exists a Positive Constant δ Such That If mentioning
confidence: 99%
“…in [27] it is showed that a symmetric D-solution (1.13) to (1.2), uniformly vanishing at infinity, exists under the only natural assumption that a satisfies (1.13) and natural regularity conditions. Note that (1.13) meets the mean property (1.12) with u 0 = 0.…”
Section: Introductionmentioning
confidence: 99%